Knowledge, attitude, and practice regarding antibiotic use and resistance among medical students in Colombia: a cross-sectional descriptive study (2020)
Background This study was designed to describe the knowledge, attitude, and practice regarding antibiotic use and resistance among medical students in Medellín, Colombia. Methods A cross-sectional study was conducted among medical students from three universities from September to December 2018. The sample size was calculated, the classrooms were visited, and those students who were willing to participate were invited to do so. The data collection instrument was constructed in three stages: i) the literature was systematically reviewed, ii) the items from the studies identified were extracted, and iii) item reduction was performed with exploratory factor analysis. Data were analyzed by calculating absolute and relative frequencies and means for quantitative variables. The indexes of knowledge, attitude, and practice were transformed to a scale from 0 (worst possible score) to 100. Comparisons were performed using the Mann-Whitney U test, Kruskall-Wallis H test, and linear regressions. Results Five hundred and thirty-two medical students were included with a response rate of 96%. Of the total participants, 49.1% reported having used antibiotics within the past year. Regarding knowledge, only 18.2% had heard of the term “antimicrobial stewardship” and 69.3% were aware that empiric antibiotic therapy contributes to antibiotic resistance. Regarding attitude, 11.6% considered that antibiotics should be discontinued as soon as symptoms disappear and 24.6% stated that it is better to prescribe broad-spectrum antibiotics to ensure that the patient is cured. Regarding practice, 28.5% recognized that resistance is a multifactorial problem, but they do not act on it because they consider that individual actions would have little impact. The adjusted linear regression showed that the variables associated with knowledge, attitude, and practice were socioeconomic status, training cycle, university, previous experience of research or education, the general perception of the training received, and antibiotic consumption. Conclusion Knowledge, attitude, and practice differ widely depending on the university, training cycle, and socioeconomic status, and a significant proportion of students consider that the standard of training received at the university on antibiotics and bacterial resistance is poor or mediocre. These findings show that there is a need to strengthen the medical students’ curriculum on antibiotics, mechanisms of antibiotic resistance, and the prudent use of antibiotics as an important strategy to combat problem-resistant public health, primarily in endemic countries.